Cover Image. Issue 8 (30th September 2018) - Unknown
Abstract : This special issue of Biopolymers is dedicated to the memory and impact of Jack Aviv, in recognition of his legendary ability to enable world‐wide scientific discovery through the design and fabrication of unique instrumentation. Jack was an amazingly compassionate human being, who treated his professional clients as though they were part of his extended family. Jack's humanity, technical expertise and philanthropy remain part of the fabric of the worldwide research community.